GLP-1RAs caused gastrointestinal adverse reactions of drug withdrawal: a system review and network meta-analysis - Zhang, Ziqi; Zhang, Qiling; Tan, Ying; Chen, Yu; Zhou, Xiqiao; Liu, Su; Yu, Jiangyi (Frontiers in Endocrinology, 2023)
Background Glucagon-like peptide-1 receptor agonists (GLP-1RAs) significantly reduce postprandial blood glucose, inhibit appetite, and delay gastrointestinal emptying. However, it is controversial that some patients are intolerant to GLP-1RAs. Methods PubMed, Embase, Web of Science, and Cochrane Library were searched for randomized controlled trials (RCTs) using GLP-1RAs with documented withdrawal due to gastrointestinal adverse reactions (GI AEs) from their inception to September 28, 2022. After extracting the information incorporated into the studies, a random-effects network meta-analysis was performed within a frequentist framework. Results 64 RCTs were finally enrolled, which included six major categories of the GLP-1RA. The sample size of the GLP-1RAs treatment group was 16,783 cases. The risk of intolerable gastrointestinal adverse reactions of Liraglutide and Semaglutide was higher than that of Dulaglutide. Meanwhile, the higher the dose of the same GLP-1RA preparation, the more likely to cause these adverse reactions. These intolerable GI AEs were not significantly related to drug homology or formulations and may be related to the degree of suppression of the appetite center. Conclusion Dulaglutide caused the lowest intolerable GI AEs, while Liraglutide and Semaglutide were the highest. For Semaglutide, the higher the dose, the more likely it is to drive GI AEs. Meanwhile, the risk of these GI AEs is independent of the different formulations of the drug. All these findings can effectively guide individualized treatment. Systematic review registration https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42022359346, identifier CRD42022359346.